Development of N-Benzamidothioureas as a New Generation of Thiourea-Based Receptors for Anion Recognition and Sensing - Nie, Li; Li, Zhao; Han, Jie; Zhang, Xuan; Yang, Rui; Liu, Wen-Xia; Wu, Fang-Ying; Xie, Jian-Wei; Zhao, Yu-Fen; Jiang, Yun-Bao (Journal of organic chemistry, 2004)
A series of neutral N-(substituted-benzamido)-N ‘-phenylthioureas (substituent = p-OC2H5, p-CH3, m-CH3, H, p-Cl, p-Br, m-Cl, and p-NO2) were designed as anion receptors, in which the thiourea binding site was attached to the benzamido moiety via an N−N bond. The absorption spectra of these N-benzamidothioureas in acetonitrile peaked at ca. 270 nm were found to show unprecedented red shifts by 7 373 to 14 325 cm-1 in the presence of anions such as AcO-, F-, and H2PO4 -. Under the same conditions, the classic neutral thiourea receptors, N-(substituted-phenyl)-N‘-phenylthioureas, showed absorption spectral shifts in most cases of less than 800 cm-1 with one exception of 6501 cm-1. Control experiments, effects of protic solvent, and 1H NMR titration confirmed the formation of hydrogen-bonding complexes between the new N-benzamidothiourea receptors and anions. The binding constants with AcO-, for example, are at 105−107 mol-1 L order of magnitude, which are 13 to 590 times those of the corresponding classic N-phenylthioureas in the same solvent. It was found that, whereas the absorption of the N-benzamidothiourea receptors showed essentially no dependence on the substituent, the substantially red-shifted new absorption band of the N-benzamidothiourea−anion binding complex was sensitively subject to the substituent. A linear relationship was found between the absorption energies of the N-benzamidothiourea−acetate binding complexes and the Hammett constants of the substituents with a negative slope of −0.34 eV. This led to the assignment that the substantially red-shifted absorption band was the ground-state intramolecular charge-transfer absorption with the substituent locating in the electron acceptor moiety. It was concluded that anion binding to the thiourea moiety of the N-benzamidothiourea receptors switched on their ground-state charge transfer. An anion-binding induced structural change was suggested to occur around the N−N bond in N-benzamidothioureas, which resulted in a substantially increased electron donating ability of the electron donor in the receptor molecules. As a consequence, the ground-state charge transfer takes place in the N-benzamidothiourea−anion binding complexes, leading to unprecedented red shifts in the absorption spectra and substantially enhanced anion binding affinities than those of the corresponding N-phenylthiourea receptors. N-Benzamido-N ‘-phenylthioureas represent a new generation of neutral thiourea-based anion receptors that show substantially improved anion binding performance important for anion sensing and recognition.